Towards 'MFL for all' in England: a historical perspective. Issue 1 (1st January 2018) - Dobson, Alan
ABSTRACT: This article considers the provision of modern foreign languages (MFL) in England since the 1970s in the context of wider curricular change and also taking into account Europe-wide developments in MFL. It charts the changes implemented over almost three decades to England's National Curriculum for MFL at secondary level (from ages 11 to 16) and highlights the significant role – particularly before 2010 – of Her Majesty's Inspectors of Schools (HMI) in evaluating curricular innovation and support for MFL teacher development. Perennial issues over this period include: the range of languages studied; the gender bias in the uptake of MFL; the low uptake of MFL after the age of 14; use of the target language and the role of grammar. The article highlights the limitations for MFL in England resulting from restricted time allocations; the lack of coherence and continuity in policy implementation; and the recent loss of support infrastructure for MFL teachers. Finally, the author reflects on the UK's participation in Council of Europe and European Union projects and the extent to which MFL in England has been influenced by these.